2014
DOI: 10.1002/jsfa.6655
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the liposoluble fraction of common wheat (Triticum aestivum ) and spelt (T. aestivum ssp. spelta ) flours using multivariate analysis

Abstract: Comparison of chromatogram areas for non-saponifiable lipid fraction between common and spelt wheat showed a statistically high difference and hence has a potential for use in authenticity control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Multivariate Principal Component analysis (PCA) of “bioactive phytochemicals” (phenolic acids, alkylresorcinols, tocols, sterols, folates, betaine, choline), dietary fibre components ( Shewry et al., 2013 ) and polar metabolites ( Shewry et al., 2017 ) showed only partial discrimination between the ancient and modern types of wheat. By contrast, Bodroza-Solarov et al (2014) discriminated between wholemeal flours of 7 bread wheats and 10 spelts by multivariate analyses based on GC-MS analysis of lipophilic components. A more recent study reported metabolomic profiling of finely milled whole grains of 77 accessions of emmer, einkorn and spelt grown in replicated randomised field trials on two sites for two years, including conventional and organic plots on one site ( Righetti et al., 2016 ).…”
Section: Factors Affecting the Composition Of Wheat Grainmentioning
confidence: 95%
“…Multivariate Principal Component analysis (PCA) of “bioactive phytochemicals” (phenolic acids, alkylresorcinols, tocols, sterols, folates, betaine, choline), dietary fibre components ( Shewry et al., 2013 ) and polar metabolites ( Shewry et al., 2017 ) showed only partial discrimination between the ancient and modern types of wheat. By contrast, Bodroza-Solarov et al (2014) discriminated between wholemeal flours of 7 bread wheats and 10 spelts by multivariate analyses based on GC-MS analysis of lipophilic components. A more recent study reported metabolomic profiling of finely milled whole grains of 77 accessions of emmer, einkorn and spelt grown in replicated randomised field trials on two sites for two years, including conventional and organic plots on one site ( Righetti et al., 2016 ).…”
Section: Factors Affecting the Composition Of Wheat Grainmentioning
confidence: 95%
“…Regarding the lipid content of spelt wheat flour [30], reported that compared to the common wheat, the lipid's spelt content is higher and varies between 7-30% and palmitic acid, oleic acid, linoleic acid and linolenic acid are the main fatty acids from spelt wheat.…”
Section: Fatty Acids Methyl Esters Content Of Spent Malt Rootlets Flomentioning
confidence: 99%
“…In Serbia, extensive surveys were carried out on the quality of spelt wheat kernels, (VUČKOVIĆ et al, 2013;FILIPČEV et al, 2013;BODROŽA SOLAROV et al, 2014;KRULJ et al, 2016), while there is less data on the agronomic properties of this crop (UGRENOVIĆ, 2013;JANKOVIĆ et al, 2015).…”
Section: Introductionmentioning
confidence: 99%